2002
DOI: 10.2298/mpns0206225p
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological examination of gallbladder contents

Abstract: E. coli, Klebsiella and Staphylococcus participate with 75.85% of all bacteriologic findings, whereas all the others make 24.15%; Amikacin, Cefalexin, Ceftriaxone, Ofloxacin and Pefloxacin are recommended in premedication; considering the fact that new generation antibiotics have not been tested yet, they were not taken into consideration for this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Although to our knowledge there is no information in the literature regarding the pathogenic role of C freundii in the development of infections in patients with AP, this bacteria has been shown to translocate in different experimental and clinical situations 37 47 48 and it is related to both biliary and intra-abdominal infections. [49][50][51][52] As bactDNA detection and identification in patients with AP is a new approach to the study of BT in humans, we do not know if C freundii is a frequent translocating agent in patients with AP.…”
Section: Discussionmentioning
confidence: 99%
“…Although to our knowledge there is no information in the literature regarding the pathogenic role of C freundii in the development of infections in patients with AP, this bacteria has been shown to translocate in different experimental and clinical situations 37 47 48 and it is related to both biliary and intra-abdominal infections. [49][50][51][52] As bactDNA detection and identification in patients with AP is a new approach to the study of BT in humans, we do not know if C freundii is a frequent translocating agent in patients with AP.…”
Section: Discussionmentioning
confidence: 99%
“…It rarely causes infective endocarditis [7]. Petakovic et al [8] reported that Escherichia coli is the most frequently isolated organism in patients with cholecystectomy (55.2%). Enterobacter species are isolated in less than 1.7% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Amikasin, sefotaksim, seftazidim ve ampisilin-sulbaktam E.coli ve K.pneumoniae'ye karşı etkili bulunurken, P.aeruginosa için 3. kuşak antipsödomonal sefalosporinler veya florokinolonların etkili olacağı bildirilmiştir (13) . Görüldüğü gibi safra kültürlerinde en sık üreyen mikroorganizmalar başta E.coli ve K.pneumoniae olmak üzere Gram negatif enterik çomaklardır (6,7,8,17,18,22) . Biliyer sisteme yönelik invazif cerrahi girişimlerin ve biliyer stent kullanımının artmasıyla birlikte P.aeruginosa'nın görülme sıklığının arttığı belirtilmiştir (4,13) .…”
Section: Gram Negatif Bakteriler N:26unclassified